2023
DOI: 10.1101/2023.11.28.568960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Episodic and associative memory from spatial scaffolds in the hippocampus

Sarthak Chandra,
Sugandha Sharma,
Rishidev Chaudhuri
et al.

Abstract: Hippocampal circuits in the brain enable two distinct cognitive functions: construction of spatial maps for navigation and storage of sequential episodic memories. This dual role of the hippocampus remains an enduring enigma. While there have been advances in modeling the spatial representation properties of the hippocampus, we lack good models of its role in episodic memory. Here we present a neocortical-entorhinal-hippocampal network model that exhibits high-capacity general associative memory, spatial memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 146 publications
(382 reference statements)
0
1
0
Order By: Relevance
“…Empirical evidence suggests that, for spatial information, this is accomplished in the brain by encoding the organism’s spatial position using a periodic code consisting of different frequencies and phases (akin to a Fourier transform of the space). Although grid cells were discovered for representations of space ( Hafting et al, 2005 ; Sreenivasan and Fiete, 2011 ; Mathis et al, 2012 ) and used for guiding spatial behavior ( Erdem and Hasselmo, 2014 ; Bush et al, 2015 ), they have since been identified in non-spatial domains, such as auditory tones ( Aronov et al, 2017 ), odor ( Bao et al, 2019 ), episodic memory ( Chandra et al, 2023 ), and conceptual dimensions ( Constantinescu et al, 2016 ). These findings suggest that the coding scheme used by grid cells may serve as a general representation of metric structure that may be exploited for reasoning about the abstract conceptual dimensions required for higher-level reasoning tasks, such as analogy and mathematics ( McNamee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence suggests that, for spatial information, this is accomplished in the brain by encoding the organism’s spatial position using a periodic code consisting of different frequencies and phases (akin to a Fourier transform of the space). Although grid cells were discovered for representations of space ( Hafting et al, 2005 ; Sreenivasan and Fiete, 2011 ; Mathis et al, 2012 ) and used for guiding spatial behavior ( Erdem and Hasselmo, 2014 ; Bush et al, 2015 ), they have since been identified in non-spatial domains, such as auditory tones ( Aronov et al, 2017 ), odor ( Bao et al, 2019 ), episodic memory ( Chandra et al, 2023 ), and conceptual dimensions ( Constantinescu et al, 2016 ). These findings suggest that the coding scheme used by grid cells may serve as a general representation of metric structure that may be exploited for reasoning about the abstract conceptual dimensions required for higher-level reasoning tasks, such as analogy and mathematics ( McNamee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%